Performance Analysis of Unsignalized Intersections Based on PKJI 2023 (Case Study: Imam Bonjol – Taman – Waru Road, Sidoarjo) - Lisa Vatma Ningsih; Nugroho Utomo; Aulia Dewi Fatikasari (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
The growth of population and motorized vehicles in Sidoarjo Regency has led to an increase in traffic volume, which impacts the performance of intersections, particularly unsignalized intersections. This study aims to analyze the performance of the unsignalized intersection at Jalan Imam Bonjol – Taman – Waru based on the Indonesian Highway Capacity Manual (PKJI) 2023 and to propose improvement strategies. The research method involves field surveys using manual traffic counting conducted over three days during peak hours, including data on traffic volume, intersection geometry, and vehicle characteristics. The analysis covers traffic volume, intersection capacity, and degree of saturation (DS). The results show that the existing condition has a DS value of 0.86 with an average delay of 14.71 seconds/pcu, indicating that the intersection is operating under saturated conditions and does not meet the acceptable standard (DS < 0.85). Therefore, an improvement strategy is proposed by converting the intersection into a signalized intersection with a three-phase system. The results indicate a significant improvement, with the DS decreasing to 0.61, resulting in a more stable, efficient, and controlled traffic condition. Thus, the implementation of traffic signals is recommended to improve performance, traffic flow, and safety at the study location. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-being:SDG 9: Industry, Innovation, and Infrastructure:SDG 11: Sustainable Cities and CommunitiesSDG 12: Responsible Consumption and Production